Prevalence, Risk Factors, and Psychosocial Impact of Restless Legs Syndrome in End-Stage Renal Disease Patients Undergoing Hemodialysis – A Cross-Sectional Study - Alamanda Venkata Anupama; Anish Mehta; Mahendra Javali; Mahesh Eswarappa; Pradeep Rangaiah; Purushottam Acharya (Annals of Indian Academy of Neurology, 2025)
Background and Objectives: Restless legs syndrome (RLS) is common but often underdiagnosed in patients with end-stage renal disease (ESRD) undergoing hemodialysis, significantly impacting their quality of life. This study investigates the prevalence, risk factors, and psychosocial effects of RLS in this population. Methods: A cross-sectional study was conducted among 308 hemodialysis patients at a tertiary care hospital. RLS was diagnosed based on the International Restless Legs Syndrome Study Group criteria. The severity of RLS, sleep quality, and mental health were assessed using the International Restless Legs Syndrome (IRLS) Severity Score, Pittsburgh Sleep Quality Index, and Hospital Anxiety and Depression Scale. Clinical and biochemical parameters were also analyzed. Statistical significance was determined using Chi-squared and unpaired t-tests (P < 0.05). Results: RLS was identified in 46 patients (14.9%). Among them, 56.6% had mild symptoms, 41.3% had moderate symptoms, and 2.1% had severe symptoms. Patients with RLS were younger (50.15 ± 12.19 vs. 57.41 ± 13.43 years, P = 0.001) and had lower body weight (57.89 ± 9.64 vs. 62.78 ± 10.58 kg, P = 0.03). Anxiety and depression were significantly higher in the RLS group (P = 0.001). Poor sleep quality was reported in 97.8% of RLS patients (P = 0.001). Hemoglobin (P = 0.02) and thyroid-stimulating hormone (P = 0.03) levels also differed significantly between groups. Conclusions: RLS is highly prevalent in ESRD patients undergoing hemodialysis and is associated with significant psychosocial burden and poor sleep quality.